In Vitro Interaction between Isavuconazole and Tacrolimus, Cyclosporin A, or Sirolimus against Aspergillus Species - Schwarz, Patrick (J Fungi (Basel), 2020)
The interaction of isavuconazole with immunosuppressors (tacrolimus, cyclosporin A, or sirolimus) against 30 Aspergillus isolates belonging to the most common species responsible for invasive aspergillosis in humans (Aspergillus flavus, Aspergillus fumigatus, Aspergillus nidulans, Aspergillus niger, and Aspergillus terreus) was evaluated in vitro by a microdilution checkerboard technique based on the EUCAST reference method for antifungal susceptibility testing. The interpretation of the results was performed based on the fractional inhibitory concentration index. The combination of isavuconazole with tacrolimus, cyclosporin A, or sirolimus, was synergistic for 56, 20, or 10% of the isolates, respectively. Interestingly synergy of the combination of isavuconazole with tacrolimus was also achieved for the majority of azole-resistant isolates of A. fumigatus, and for all A. niger isolates with isavuconazole minimal inhibitory concentrations ≥ 8 µg/mL. Antagonistic interactions were never observed for any combination tested.